2015
DOI: 10.1094/pdis-09-14-0993-re
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sensitivity of Didymella bryoniae to Cyprodinil and Fludioxonil and Field Efficacy of these Fungicides Against Isolates Resistant to Pyraclostrobin and Boscalid

Abstract: Keinath, A. P. 2015. Baseline sensitivity of Didymella bryoniae to cyprodinil and fludioxonil and field efficacy of these fungicides against isolates resistant to pyraclostrobin and boscalid. Plant Dis. 99:815-822.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…TCZ [(RS)-1-p-chlorophenyl-4,4-dimethyl-3-(1H-1,2,4-triazol-1-yl methyl)pentan-3-ol] is a systemic triazole fungicide which is used for the control of a range of plant fungal pathogens in different crops including winter cereals (D'Angelo et al, 2014;Keinath, 2015). It is rather persistent in the soil environment with DT 50s ranging from 49 to 610 days (Strickland et al, 2004;EFSA, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TCZ [(RS)-1-p-chlorophenyl-4,4-dimethyl-3-(1H-1,2,4-triazol-1-yl methyl)pentan-3-ol] is a systemic triazole fungicide which is used for the control of a range of plant fungal pathogens in different crops including winter cereals (D'Angelo et al, 2014;Keinath, 2015). It is rather persistent in the soil environment with DT 50s ranging from 49 to 610 days (Strickland et al, 2004;EFSA, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gummy stem blight (GSB) is one of the most destructive diseases in cucurbits worldwide, especially for melon (Keinath, 2011;Keinath, 2015). In Brazil, GSB is one of the most damaging diseases in melon fields (Gasparotto, Vida, Tessmann, & Alves, 2011;Cardon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control has been used to minimize the plant losses; however, even recommended fungicides have shown problems, such as low efficacy and resistance of the pathogen to some chemical groups, including benzimidazoles and thiophanates, pyrimidines-carboxamides, and methoxycarbamates (Keinath, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ascomycete D. bryoniae is one of the most relevant pathogens in the world, causing significant economic losses to the Cucurbitaceae family, particularly melon, watermelon and cucumber (Babu et al, 2015;Keinath, 2015). Gasparotto et al (2011) reported that gummy stem blight is the most devastating disease in melon (Cucumis melo var.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of appearance of pathogen resistance to systemic fungicides based on benzimidazole and thiofanate, pyrimidine-carboxamide, methoxy-carbamates, which are used to control D. bryoniae in various cucurbits, especially in melons and watermelons (Keinath, 2015).…”
Section: Introductionmentioning
confidence: 99%